2010
DOI: 10.1016/j.bcp.2010.07.041
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin: A pleiotropic molecule regulating inflammation

Abstract: Melatonin is a neurohormone produced by the pineal gland that regulates sleep and circadian functions. Melatonin also regulates inflammatory and immune processes acting as both an activator and inhibitor of these responses. Melatonin demonstrates endocrine, but also paracrine and autocrine effects in the leukocyte compartment: on one side, leukocytes respond to melatonin in a circadian fashion; on the other side, leukocytes are able to synthesize melatonin by themselves.With its endocrine and paracrine effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
247
0
12

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(273 citation statements)
references
References 127 publications
(154 reference statements)
4
247
0
12
Order By: Relevance
“…33 Melatonin also has immunomodulatory and antiinflammatory effects. 34,35 We found that nocturnal melatonin levels were significantly higher in the patients with AD compared with the controls. It is also our novel finding that in patients with AD, a higher nocturnal melatonin level was associated with better sleep efficiency, less sleep fragmentation, and milder disease severity.…”
Section: Figurementioning
confidence: 78%
“…33 Melatonin also has immunomodulatory and antiinflammatory effects. 34,35 We found that nocturnal melatonin levels were significantly higher in the patients with AD compared with the controls. It is also our novel finding that in patients with AD, a higher nocturnal melatonin level was associated with better sleep efficiency, less sleep fragmentation, and milder disease severity.…”
Section: Figurementioning
confidence: 78%
“…Melatonin and its metabolites directly scavenge free radicals [15] and stimulate the activity and expression of antioxidant enzymes [23][24][25]. It also decreases production of proinflammatory cytokines by suppressing the mRNA expression of TNF-α, IL-1β, IL-6, and iNOS [17,26,27]. The overall findings indicate the efficacy of using melatonin as a therapeutic tool to prevent obesity-related disorders.…”
Section: A Double-blind Placebo-controlled Trial Related To the Effementioning
confidence: 89%
“…During the past decade, several studies have supported the potential health benefits of melatonin including antioxidation, anti-inflammatory, immunomodulatory, body fat mass, and weight regulatory effects [10][11][12][13][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Agomelatine is a a b c d member of a novel class of new antidepressants which are melatonin agonists; it has been approved by the European Union, after being shown to have similar efficacy to SSRIs for the treatment of depression [96,97]. Melatonin agonists have numerous effects on the immune system, most of which serve to limit inflammation [98]. Finally, nonpharmacologic approaches are also used to treat depression; these approaches include vagal nerve stimulation and exercise.…”
Section: Therapeutic Approaches To the Treatment Of Depression: A Focmentioning
confidence: 99%